Cultural group differences in the association of neural sensitivity to social feedback and social anxiety among diverse adolescents. (November 2021) - Rapp, Amy M.; Tan, Patricia Z.; Grammer, Jennie K.; Gehring, William J.; Miller, Gregory A.; Chavira, Denise A.
Abstract: Social anxiety disproportionately impacts individuals from certain cultural and developmental groups, namely those from Latinx and Asian American cultures and adolescents. Neural sensitivity to social feedback has been shown to vary across individuals and could contribute to this disparity by further exacerbating differences; thus, this could be an important phenomenon for understanding, preventing, and treating social anxiety. The goal of the present study was to examine the association of social anxiety with a neural correlate of feedback processing, the feedback-related negativity (FRN), and determine if there was a moderating effect of racial/ethnic group. A community sample of 104 Latinx ( n  = 41), Asian American ( n  = 24), and non-Latinx White (NLW; n  = 39) adolescents (ages 13–17) completed a computerized peer feedback task while continuous electroencephalogram was recorded. Social anxiety and FRN measures were differentially associated as a function of race/ethnicity. NLW adolescents demonstrated greater FRN responses to acceptance feedback as social anxiety increased, whereas FRN responses to both rejection and acceptance feedback were related to greater social anxiety for Asian American adolescents. Notably, the Latinx group showed the greatest FRN responses yet endorsed the least amount of social anxiety, with no relation between social anxiety and FRN detected. Results highlight cultural variation in the relation between neural correlates of self-regulatory processes and social anxiety. This information could guide culturally-informed models of social anxiety that adopt a multiple units of analysis framework.